PENGARUH METODE MENGAJAR DAN INTENSITAS ASESMEN GURU TERHADAP HASIL BELAJAR SISWA BIDANG STUDI PAI - ANHUSADAR, LA ODE (JURNAL PENDIDIKAN ANAK USIA DINI, 2012)
The purpose of this study was to determine whether students field of study is influenced by the Islamic Education teachers teaching methods and intensity of teacher assessments in class 1 SDN 1 Poasia Kendari. Study with a sample of 40 people. This research used Ex Post Facto and analysis of descriptive and inferential data. Descriptive analysis is used to present data in the form of histograms, graphs, calculation of mean, median, mode, standard deviation, and the theoretical range of each variable. Inferential analysis is then performed to test the hypothesis through the analysis of variance (ANAVA) with two factors. The results indicate that there are significant differences in the stimulation of teaching methods of teachers using the method of administration tasks and methods of lecture, there were no differences in the method of administration tasks through the lecture method of assessment of high intensity, there is no difference in the method of administration tasks through the lecture method of assessment of low intensity and there is nointeraction effect of teachers teaching methods and intensity of assessment of learning outcomes of students in class 1 SDN 1 Poasia Kendari.Keywords: teaching methods, intensity of teacher assessments